Efforts to improve activities and results of student learning in civic education learning through Cooperative Learning model of Jigsaw type - Yuli Zarnita; Azwar Ananda; Khairani Khairani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2019)
This research is motivated by the low activity and student learning outcomes in  Civic Education  subjects in class 11th social program 2 at Islamic Senior High School Number 2  Bukittinggi. The factors that cause low activity and student learning outcomes such as the lack of opportunities for students to explore potential, low motivation, learning models that are not varied. The purpose of this study was to obtain information on the increase in activity and student learning outcomes through the jigsaw type learning cooperative learning model in class 11th social program 2 at Islamic Senior High School Number 2  Bukittinggi. The type of this research is Classroom Action Research (CAR). The subject of the research was 25 people consisting of 18 female students and 7 male students. Based on the results of the study showed that there was an increase in activity in the first cycle of reading 60%, discussing 64%, listening to 64%, presenting 49.3%, asking 60%, making a summary of 26.67%, working on the test 42.67%. In cycle II I read 86.3%, discussed 86%, listened to 86%, presented 75.67, asked 83.67, made a summary of 68.33% and worked on the test 80%. From the results of the study it can be concluded that Civics learning using the jigsaw type learning cooperative learning model can improve learning activities and student learning outcomes in class 11th social program 2 at Islamic Senior High School Number 2  Bukittinggi.